Rancang Bangun Sistem Informasi Administrasi Publik Berbasis Website di Desa Panyadap - Armansyah M. Sarusu; Miki Wijana; Fanny Mochammad Abdul Rhozak (Ma'soem University, 2022)
Panyadap Village which are Village Government Agencies whose duties are to collect population data, Make Family Cards, Birth Certificates, Death Certificates, Certificates Moving, Business Certificate and others. The public administration system in the Panyadap village administration is still manual or semi-computerized, not yet making full use of Information Technology. So that the process of public service becomes difficult and slow. With the creation of a Website-Based Public Administration Information System Design, it can make it easier for staff or officers to do their work. Make it easier for members of the public to know and be more thorough about the requirements when submitting correspondence so that services become more effective and efficient.